2005
DOI: 10.1509/jmkg.69.3.66.66368
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Influence Strategies: Argument Structure and Dependence as Determinants of the Effectiveness of Influence Strategies in Gaining Channel Member Compliance

Abstract: Although there is considerable research examining the effects of influence strategies on relational outcomes, research has been silent on the effectiveness of influence strategies in achieving the primary objective: channel member compliance. The authors develop a theoretical model that predicts that noncoercive influence strategies (Rationality, Recommendations, Information Exchange, and Requests) with an argument structure that contains more thorough content result in relatively greater levels of compliance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(178 citation statements)
references
References 48 publications
3
173
0
2
Order By: Relevance
“…The theory on power and dependence discusses the importance of maintaining an equilibrium in supply chain relationships (Dwyer et al 1987;Liu et al 2009;Payan and McFarland 2005;) and while we found that the interdependence was a key reason why the partners remained in the relationship (Cannon et al 2010), when a supply chain member gained perceived advantage they attempted to use that power. So, even while interdependence existed, opportunistic behaviours were exposed.…”
Section: Propositionmentioning
confidence: 68%
“…The theory on power and dependence discusses the importance of maintaining an equilibrium in supply chain relationships (Dwyer et al 1987;Liu et al 2009;Payan and McFarland 2005;) and while we found that the interdependence was a key reason why the partners remained in the relationship (Cannon et al 2010), when a supply chain member gained perceived advantage they attempted to use that power. So, even while interdependence existed, opportunistic behaviours were exposed.…”
Section: Propositionmentioning
confidence: 68%
“…The reliability of the scale was calculated using Cronbach's Alpha which was 90%. In order to measure satisfaction, we browed and modified two items from Payan and McFarland, (2005) and one each from Kumar et al (1992) and Razzaque and Boon, (2003). The items were chosen to express overall satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…affective and psychosocial) aspects of the relationship (Geyskens et al 1999;Geyskens and Steenkamp, 2000). Another view (Payan and McFarland, 2005) accepts satisfaction as the overall satisfaction and/or happiness in the relationship between firms. In this study we considered overall satisfaction about the all aspects of the relationship.…”
Section: Channel Satisfaction and Firm Performancementioning
confidence: 99%
“…In a retail context, interpersonal influence depicts a retail buyer's ability and efficacy to modify trading partners' behaviors by gaining compliance toward a particular course of action (Frazier & Summers, 1984;Payan & McFarland, 2005). When social networks are involved, perceptions and attributions about such behaviors are enhanced if the individual gaining compliance is believed to be tied to other prominent individuals in the network (Kilduff & Krackhardt, 1994).…”
Section: The Importance Of Interpersonal Influence In Network Settingsmentioning
confidence: 99%